(−)-Meptazinol–melatonin hybrids as novel dual inhibitors of cholinesterases and amyloid-β aggregation with high antioxidant potency for Alzheimer's therapy. Issue 13 (1st July 2015) - Cheng, Shaobing; Zheng, Wei; Gong, Ping; Zhou, Qiang; Xie, Qiong; Yu, Lining; Zhang, Peiyi; Chen, Liangkang; Li, Juan; Chen, Jianxing; Chen, Hailin; Chen, Hongzhuan
Graphical abstract: Abstract: The multifactorial pathogenesis of Alzheimer's disease (AD) implicates that multi-target-directed ligands (MTDLs) intervention may represent a promising therapy for AD. Amyloid-β (Aβ) aggregation and oxidative stress, two prominent neuropathological hallmarks in patients, play crucial roles in the neurotoxic cascade of this disease. In the present study, a series of novel (−)-meptazinol–melatonin hybrids were designed, synthesized and biologically characterized as potential MTDLs against AD. Among them, hybrids7 –7c displayed higher dual inhibitory potency toward cholinesterases (ChEs) and better oxygen radical absorbance capacity (ORAC) than the parental drugs. Furthermore, compound7c could effectively inhibit Aβ self-aggregation, showed favorable safety and the blood–brain barrier (BBB) permeability. Therefore, 7c may serve as a valuable candidate that is worthy of further investigations in the treatment of AD.